FAKTOR – FAKTOR YANG MEMENGARUHI KEPATUHAN IBU HAMIL MENGONSUMSI TABLET FE DI BPM ISNIWATI SUKOHARJO - Sumi Anggraeni (Universitas Jenderal Achmad Yani Yogyakarta, 2019)
Background : Anemia prevalent is highest enough in pregnancy can risk the premature birth, birth bleeding risk, and the baby low birth. It is very important for maternity to loyalty for consuming Fe tablet to fulfil iron as long as pregnancy because iron has important role for baby growth. Consume an Iron supplement while pregnancy can fulfil iron necessity, increase body immunity and prevent the anemia to maternity. Objective : This research aims to know the factors that influence maternity loyalty to consume Fe tablet in Isniwati BPM Sukoharjo. Methode : This research used analytic observational with crossectional approach. The sample in this research is all of maternity who visited in Isniwati BPM and the total is 53 maternities who had fulfilled the criteria of inclusion and exclusion. Data analyse was using chi square in bivariat analyse. Result : The result of statistic test showed the relation that has mean toward knowledge (p value = 0.009) and antenatal visitation (p value = 0.025) then family support (p value = 0.305) and motivation (p value = 0.833) and showed the relation that has not mean with give the suggestion by leaflet and information such as street banner to give the wide knowledge in order to create the family positive support and motivating family to help maternity in consume iron tablet. Conclusion: The factor that influence maternity loyalty to consume fe tablet in isniwati bpm sukoharjo are knowledge and antenatal care visits. Keyword : Fe Tablet, Loyalty, Pregnanc